Effect of transcutaneous electrical nerve stimulation on labour pain relief among primigravida and multigravida mothers - Veyilmuthu, Ramamoorthy; Govindan, Sumathi; Venugopalan, Mahalakshmi; Panicker, Seetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: TENS by neuro-physiological means seems to help in relieving labour pain. Most of the pregnant women are not aware of the coping strategies for labour pain. As a result they tend to be restless and stress themselves by shouting or screaming due to pain. By using TENS, women in labour can save their energy without stressing themselves and make use of the saved energy for pushing the fetus during the second stage of labour. The objective was to analyze the effect of TENS on relieving labour pain among the postnatal mothers who had used TENS to cope up with the labour pain. Methods: Data collected from 1041 women [Primipara (n=702) and Multipara (n=339)] who used TENS to cope up pain throughout the labour was used for this retrospective study. Results: 88% of women had vaginal delivery and only 12% of women had cesarean section. More than 50% of both primiparous and multiparous women who had normal and vacuum assisted vaginal delivery experienced excellent pain relief using TENS. Almost 40 % of both primiparous and multiparous women who had forceps delivery and lower segment cesarean section experienced excellent pain relief using TENS. Except 2% of women with normal vaginal delivery, none of them stated that there was no relief of pain using TENS. Conclusions: TENS had a very good effect in coping up the labour pain and could be used during the first and second stages of labour.